Depositional conditions during the Lower Kellwasser Event (Late Frasnian) in the deep‐shelf Łysogóry Basin of the Holy Cross Mountains Poland. (25th March 2016) - Rakociński, Michał; Pisarzowska, Agnieszka; Janiszewska, Katarzyna; Szrek, Piotr
Abstract : Integrated biostratigraphical, microfacial and geochemical studies of the Lower Kellwasser Event in the Płucki succession (southern Poland) provide details about redox conditions during the deposition of this horizon in the deep‐shelf Łysogóry basin of the Holy Cross Mountains. The environment is characterized by calm sedimentation and soft, muddy carbonate substrate. However, microfacies changing from wackestones to grainstones, the presence of crushed or current‐oriented nautiloid shells and the occurrence of redeposited material from shallow‐water Dyminy Reef environments (such as calcispheroids, algae and girvanellid cyanobacteria) suggest episodes of a higher‐energy regime. Uranium/thorium ratios indicate that bottom‐water redox conditions changed periodically from being mainly anoxic in the middle part of the Lower Kellwasser Horizon to dysoxic in the lower and upper parts. During a short‐term episode of bottom‐water ventilation, the seafloor was rapidly colonized by a dense assemblage of opportunistic buchiolid bivalves, which suffered mass mortality upon the return to anoxic conditions. A very rich concentration of cephalopods and homoctenids may be regarded as reflecting a bloom of high‐density populations during high‐productivity events. Similarly, they suffered mass mortality when episodically increasing anoxia/euxinia reached the upper part of the water column. The Late Frasnian inorganic carbon isotope records in the Płucki section show a positive shift with a maximum amplitude of 3‰. This enrichment in δ 13 C can be correlated with the deposition of the Lower Kellwasser Horizon and reflects the expansion of anoxic and probably high‐productivity regimes.